Melanin nano-pigments for heavy metal remediation from water. Issue 2 (22nd January 2019) - Thaira, Harsha; Raval, Keyur; Manirethan, Vishnu; Balakrishnan, Raj Mohan
ABSTRACT: Melanins are water insoluble polyphenol compounds. The metal ion chelating property of natural melanin is exploited for removal of heavy metals from contaminated water. We optimized biosynthesis of melanin from marine bacterium using different growth media, media components, and operating conditions. Optimized medium yielded 513 mg/L melanin at 36 h of incubation, which was 3.15 times higher than the yield before optimization. Particle size analysis of the biosynthesized melanin indicated a size of 32 ± 0.98 nm. Preliminary investigation indicated that melanin nanoparticles could adsorb different heavy metals such as chromium, selenium, and lead from very low initial concentrations.